2020
DOI: 10.3934/cpaa.2020130
|View full text |Cite
|
Sign up to set email alerts
|

Stability of multi-peak symmetric stationary solutions for the Schnakenberg model with periodic heterogeneity

Abstract: In this paper, we consider the following one-dimensional Schnakenberg model with periodic heterogeneity:        ut − ε 2 uxx = dε − u + g(x)u 2 v, x ∈ (−1, 1), t > 0, εvt − Dvxx = 1 2 − c ε g(x)u 2 v, x ∈ (−1, 1), t > 0, ux(±1) = vx(±1) = 0. where d, c, D > 0 are given constants, ε > 0 is sufficiently small, and g(x) is a given positive function. Let N ≥ 1 be an arbitrary natural number. We assume that g(x) is a periodic and symmetric function, namely g(x) = g(−x) and g(x) = g(x + 2N −1). We study the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Pattern dynamics generated from Schnakenberg model have been recognized by [3][4][5][6][7][8][9][10][11] and so on. Different solutions as peaked steady states, pulses, spiky solutions and semi-analytical solutions have been widely studied by many authors and they have found much richer dynamics exhibited by the Schnakenberg model (see, for example, [12][13][14][15][16][17][18][19]). Local dynamics and bifurcation problems in Schnakenberg system have been investigated [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Pattern dynamics generated from Schnakenberg model have been recognized by [3][4][5][6][7][8][9][10][11] and so on. Different solutions as peaked steady states, pulses, spiky solutions and semi-analytical solutions have been widely studied by many authors and they have found much richer dynamics exhibited by the Schnakenberg model (see, for example, [12][13][14][15][16][17][18][19]). Local dynamics and bifurcation problems in Schnakenberg system have been investigated [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…[24] and the reference therein.) Recently, there are the study of the existence and stability of spike patterns for the Schnakenberg model on a one-dimensional interval with heterogeneity [14,10,11,1]. In these works, the effect of heterogeneity on the existence of spiky solutions and their stability were investigated.…”
mentioning
confidence: 99%